Uncertain times require new thinking for agri-food science to ensure food security and nutrition for all - Fraser, E.D.G.; Adeyemo, O.; Amiot-Carlin, M.-J.; Azam-Ali, S.; Caron, P.; Cole, M.; Clapp, J.; Duwayri, M.; Echeverría, R.; Elizondo, C.; Elver, H.; Lehman, B.; et al. (Elsevier, 2025)
For over six decades, international policy has enabled agricultural products to move relatively easily across national borders. Currently, however, the landscape is changing. Deglobalization and the erosion of multilateral principles threaten international food supply chains while climate change is increasingly undermining production. In addition, today’s food systems contribute to major environmental and human health problems. The emerging global agri-food research agenda must adapt quickly to these realities. Here we propose that a new research agenda be established based on three principles to help respond to challenging times, promote human rights, sustain gains made in the past, and support greater positive impacts in the future. Principle one – a strengthened commitment to community engagement. Principle two – better supporting interdisciplinary systems thinking. Principles three – combatting misinformation by enabling enhanced public communication. We believe that today’s crises present an opportunity to establish the foundations of a food system transformation that is more equitable, transparent, sustainable, and democratic.